Relationships Between Some Blood and MilkComponents in Early Lactation in Non-Dairy Sheep - CIMEN, M.; KARAALP, M.; SAHIN, S. (Asian Journal of Chemistry, 2010)
In the present study, the relationships between plasma and milk parameters of non-dairy Karayaka sheep in early lactation period have been investigated. Two years old, twenty Karayaka sheep were used in the experiment. The study continued for 50 d after parturition. Sheep were fed a diet containing 135.1 g crude protein and 2.31 metabolized energy kcal/kg. The cholesterol in plasma was positively correlated with milk urea (r = 0.52; p < 0.05) and negatively with milk fat (r = -0.56; p < 0.05). A significant positive correlation (r = 0.51; p < 0.05) between plasma cholesterol and milk yield was found. There was also significant positive correlation (r = 0.59; P < 0.05) between plasma and milk urea in this study. But no correlation between body measurements and milk components could be established in this study. It was concluded that the relationships for many observed parameters between plasma and milk were not dear in non-dairy sheep as much as in dairy cows.